Workplace Policies and Perinatal Depressive Symptoms Among Low‐Income Single and Partnered Working Mothers. Issue 4 (21st July 2020) - Newkirk, Katie; Perry‐Jenkins, Maureen; Laws, Holly B.; Hien, Michelle
Abstract : Objective: This study examined associations between workplace policies and maternal depression in the context of mothers' relationship status and job characteristics. Background: The associations between workplace policies and postpartum depressive symptoms may differ based on contextual factors that have received little attention in the literature. In this study, these questions are addressed in an understudied sample of low‐income working mothers. Method: Participants included 95 employed, low‐income mothers who were recruited from prenatal classes in southern New England. Mothers' self‐reported data was collected at five time points from the third trimester of pregnancy through 12 months postpartum. Multilevel structural equation modeling was used to test all study hypotheses. Results: Length of parental leave and negative spillover interacted to predict levels of depressive symptoms, such that longer leave mattered more in the context of high spillover. A moderated mediation was found, whereby schedule flexibility related to less of an increase in depressive symptoms for single mothers, whereas partnered mothers with greater schedule flexibility experienced an increase in spillover, with no net benefit to depression. Conclusion: Contextual factors, such as mothers' relationship status and the level of spillover on the job, can influence whether and how much different types of workplace policies can benefit maternal postpartum mental health. Implications: Employers also may ease the transition back to work after parental leave by taking steps to minimize negative work‐to‐family spillover for new mothers. More work needs to be done to enable partnered mothers to experience the mental health benefits of schedule flexibility policies.